The Role of Blended Learning Model in Learning for Students - Wahyu Purnomo; Dewi Syafitri; Citra Raflesia (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2022)
The COVID-19 pandemic past years is a big challenge for education worldwide because education has to be done virtually to stop the spread of the COVID-19. Diverse geographical conditions in Indonesia consisting of highlands, valleys, lowlands, mountains and some areas that are far away from cities make students difficult to connect to the internet and thus, virtual teaching is challenging. One form of learning that is able to develop independence student learning is blended learning, this learning model combines online and offline learning. This form of learning model enable students to learn effectively and efficiently, more easy access to teaching materials, and ultimately increase independence student learning because learning is done independently. This study concludes that blended learning can be considered as an efficient approach of distance learning in terms of students’ learning experience, student-student interaction as well as student instructor interaction and is likely to emerge as the predominant education model in the future. Keywords: Blended Learning; Language Learning; Learning Model